PENGARUH FEE AUDIT ABNORMAL TERHADAP KUALITAS AUDIT DENGAN ADOPSI IFRS SEBAGAI VARIABEL MODERATING - Yunita Awaliyah; Sudarno Sudarno (Diponegoro Journal of Accounting, 2019)
The focus of this study is to examine the effect of abnormal audit fee to audit quality and IFRS adoption is used to moderate its relation. Abnormal audit fee is the difference between the actual audit fee and the estimated of its normal audit fee. In this study, we use the discretionary accruals as the proxy of the audit quality. The population in this study is all the non-financial companies which registered on IDX for 2011-2013 period. We use the purposive sampling method and it obtains the 213 companies as our sample. We use the Modified Jones Model to calculate the discretionary accruals while double regression analysis is used to analyze the data. The result shows that abnormal audit fee impacts the audit quality negative significantly and IFRS adoption doesn’t impact the relation between abnormal audit fee and audit quality. This result supports the audit effort theory whereby fee audit surely reflects the auditor effort to do all the audit procedures.